Characterization of nickel oxide quantum dots as hole transport material in perovskite solar cells - Muniandy, Subathra (2024)
Perovskite solar cells (PSCs) have attracted the interest of researchers owing to their excellent light absorption, improved carrier mobility, high-power conversion efficiency and sustainable photovoltaic cell. PSCs have charge transport materials known as electron transporting layers (ETL) and hole transporting layers (HTL) that interact with the perovskite layer. The HTL is a fundamental component in PSC structures which are generally composed of a Spiro-OMeTAD and PEDOT:PSS material that has a drawback of a high cost, lengthy synthesis process, and insufficient long-term stability. Nickel oxide (NiO) as an inorganic HTL has been emphasized in PSCs owing to low cost, solution-based processing and the good band alignment as HTL in PSCs. Despite the extensive investigation of NiO, the importance of altering the pH of the precursor solution to improve the performance of HTL remains significant which have impact on the morphologies, crystal sizes, and textural qualities of the material. This project proposes a novel idea for introducing NiO quantum dots (QDs) in the HTL to achieve high efficiency and flexibility. The experimental study present the effect of the bottom and top layer of synthesized NiO at different pH values (9-12) using a spin-coating method annealed at 500 ºC, 600 ºC, and 700 ºC. The in-depth characterization of the synthesized NiO was executed by XRD, UV-Vis spectroscopy, FTIR, AFM, SEM, TEM, PL, RF Impedance Analyzer, and four point-probe to investigate their structural, optical, element composition, surface roughness, morphological, quantum size, optical emission, dielectric constant, and resistivity properties. The performance of full fabricated PSC based on NiO or PEDOT:PSS/MAPbI3/Graphene/ZnO/Ag were evaluated by current-voltage (I-V) curve. According to XRD findings, all the prominent diffraction peaks of NiO at 37.2º, 43.36º, 63.04º, and 75.51º were observed only in pH 11 at both layers. The SEM revealed the surface morphology of pH 11 have good coverage with less agglomeration of particles as compared to other pH values. The absorption spectrum of pH 11 was noticed in the UV region with band gap increasing from 3.45 to 3.64 for bottom layer and 3.42 to 3.47 for top layer. This research confirmed the quantum confinement effect obtained at pH 11 NiO through the reduction of crystallite size with higher bandgap energy. The impedance analyzer implies the layers of pH 11 NiO (700 ºC) have higher dielectric constant (7.09 for bottom layer and 7.20 for top layer) with minimal polarization effect. A strong absorption peak were observed in FTIR analysis (400cm-1 to 600cm-1), ascribed to the presence of NiO vibration. TEM analysis revealed an average particle size of about 9.82 nm and 10.6 nm for the bottom and top layer of pH 11 NiO respectively. The observation of blue shifted PL emission bands that extended from 532 nm to 550 nm into the visible area proved that pH 11 NiO has high charge transfer resistance. The inverted PSC fabricated with bottom and top layer pH 11 NiO (700 ºC) showed better performance than for the inverted PSC based on PEDOT:PSS. Based on these findings, NiO produced at pH 11 annealed at 700 ºC exhibited promising characteristics, suitable for HTL in PSCs.